Recurrent anal fistulas: Regarding 115 cases - Villalba, Joaquín (Cirugía del Uruguay, 1997)
The author makes a revision of 115 cases of recidivant anal fistulas over a total of 398 patients who underwent surgery due ot cryptoglandular anal fistulas at the 2nd. Surgical Clinic at the Hospital de Clínicas of the Facultad de Ciencias Médicas in Asuncion and at the Hospital Regional in San Lorenzo, Paraguay between august 1986 and March 1995.